2018
DOI: 10.1177/2050312118800209
|View full text |Cite
|
Sign up to set email alerts
|

Population health challenges in primary care: What are the unfinished tasks and who should do them?

Abstract: Background:There are numerous recommendations from expert sources that help guide primary care providers in cancer screening, infectious disease screening, metabolic screening, monitoring of drug levels, and chronic disease management. Little is known about the potential effort needed for a healthcare system to address these recommendations, or the patient effort needed to complete the recommendations.Methods:For 73 recommended population healthcare items, we examined each of 28,742 patients in a primary care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Because automated bulk ordering of mammograms was part of the self-scheduling process, providers were freed up to do other activities besides ordering routine mammograms. As preventive services and other chronic care services take up an increasing amount of provider time, decreasing provider time for this activity is very important [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because automated bulk ordering of mammograms was part of the self-scheduling process, providers were freed up to do other activities besides ordering routine mammograms. As preventive services and other chronic care services take up an increasing amount of provider time, decreasing provider time for this activity is very important [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, screening mammography is often just one of many recommended actions that primary care providers need to address with their patients. In a study at Mayo Clinic, we found that primary care patients aged 50-65 years, on average, had 5.5 unmet health care recommendations, with the conclusion that there needs to be “new approaches to address the burgeoning numbers of uncompleted recommendations” [ 8 ]. Yarnall et al [ 9 ] also noted the large amount of time that is required for primary care providers to address every preventive service, including screening mammography.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] It has also been used to describe routine primary care task distribution and efforts required to complete these tasks. 12…”
Section: Data Collectionmentioning
confidence: 99%